Quality management (Boston : McGraw Hill, 2005)
First ed. under title : Tools and methods for the improvement of quality, 2nd ed. authors: Howard Gitlow, Alan Oppenheim, and Rosa Oppenheim.
Keywords: Quality management -- Statistical methods